Effect of vermicompost on Black gram nutrition in Alfisol of Chhattishgarh - PATEL, UMESH KUMAR; NIRALA, HEMLATA; SINHA, JITENDRA (Journal of Soil and Water Conservation, 2021)
An experiment was conducted in 2011-2012 at the Instructional farm of Krishi Vigyan Kendra Anjora, Durg (C.G.), laid out in CRD with twelve treatments comprised of 25, 50 and 75 percent of recommended dose of nitrogen, and organic sources Vermicompost @ 2.5 & 5.0 t ha-1, were applied in Black gram crop. The results showed that the increase in doses of vermicompost from 2.5 to 5 t ha-1 also significantly increased the plant dry matter as well as yield and the highest N and P content in plant were recorded in the treatment receiving 75 percent N as urea along with 5 t ha-1 vermicompost.